2016
DOI: 10.2147/ndt.s121149
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone could induce remission in major depression: a meta-analysis

Abstract: BackgroundPioglitazone, a selective agonist of the nuclear transcription factor peroxisome proliferator-activated receptor-gamma (PPAR-γ), prescribed for the treatment of type 2 diabetes, could have antidepressant properties. However, its potential to induce remission of major depressive episodes, the optimal clinical target for an antidepressant drug, is a matter of concern. Indeed, only one out of four double-blind randomized controlled trials show higher remission rates with pioglitazone than with control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 42 publications
0
47
1
1
Order By: Relevance
“…Some interesting genes listed included FTO, which is a wellknown gene in controlling weight and energy balance (Speakman, 2015); TCF7L2, a transcription factor of key role of Wnt signaling pathway that is strongly associated with diabetes (Jin & Liu, 2008); PPARG, a target for anti-diabetic agents (notably the PPAR-gamma agonist pioglitazone was shown to be efficacious in depression (Colle et al, 2017)) and others. Some interesting genes listed included FTO, which is a wellknown gene in controlling weight and energy balance (Speakman, 2015); TCF7L2, a transcription factor of key role of Wnt signaling pathway that is strongly associated with diabetes (Jin & Liu, 2008); PPARG, a target for anti-diabetic agents (notably the PPAR-gamma agonist pioglitazone was shown to be efficacious in depression (Colle et al, 2017)) and others.…”
Section: Shared Genetic Variants and Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Some interesting genes listed included FTO, which is a wellknown gene in controlling weight and energy balance (Speakman, 2015); TCF7L2, a transcription factor of key role of Wnt signaling pathway that is strongly associated with diabetes (Jin & Liu, 2008); PPARG, a target for anti-diabetic agents (notably the PPAR-gamma agonist pioglitazone was shown to be efficacious in depression (Colle et al, 2017)) and others. Some interesting genes listed included FTO, which is a wellknown gene in controlling weight and energy balance (Speakman, 2015); TCF7L2, a transcription factor of key role of Wnt signaling pathway that is strongly associated with diabetes (Jin & Liu, 2008); PPARG, a target for anti-diabetic agents (notably the PPAR-gamma agonist pioglitazone was shown to be efficacious in depression (Colle et al, 2017)) and others.…”
Section: Shared Genetic Variants and Pathwaysmentioning
confidence: 99%
“…An example in this field is pioglitazone, an insulin sensitizer which was shown in a meta-analyses of four RCTs to be a safe and effective adjunctive medication in nondiabetic patients with MDD (Colle et al, 2017). Nevertheless, due to the computational nature and limitations as will be discussed later, the drug enrichment or repositioning analysis should be regarded as an exploratory proof-of-concept example rather than a confirmatory study.…”
Section: Drug Enrichment Analysesmentioning
confidence: 99%
“…In contrast, clinical trials showed that insulin sensitizer antidiabetic drugs activating peroxisome proliferator‐activated receptor gamma substantially reduced depressive symptoms in patients . For example, pioglitazone was found to enhance remission in patients with MDD or bipolar disorders . It was reported that pioglitazone mediated improvement in depressed patients probably through suppressing pro‐inflammatory cytokines such as IL‐6 .…”
Section: Drugs Repurposed or At The Prerepurposing Investigation Phasmentioning
confidence: 99%
“…[99] For example, pioglitazone was found to enhance remission in patients with MDD or bipolar disorders. [100] It was reported that pioglitazone mediated improvement in depressed patients probably through suppressing proinflammatory cytokines such as IL-6. [101] Moreover, neuroprotective effects have been suggested for these antidiabetic drugs.…”
Section: Drug Repurposing: Principles and Techniquesmentioning
confidence: 99%
“…In a recent metaanalyses resulting from 4 open-label trials and 4 randomized controlled trials in 448 patients peroxisome proliferator-activated receptor-gamma agonists have antidepressant effects in the 4 open-label studies and in 3 out of 4 RCT [73]. Pioglitazone, either alone or as addon therapy to conventional treatments, could induce remission of depression, suggesting that drugs with peroxisome proliferator-activated receptor-gamma agonist properties may be true and clinically relevant antidepressants, even in patients without metabolic comorbidities, improving depression with mechanisms largely unrelated to its insulin-sensitizing action [72, 74].…”
Section: In Patients With Diabetes Use Serotonin Reuptake Inhibitorsmentioning
confidence: 99%